China's impact on the global wind power industry - Rasmus Lema; Axel Berger; Hubert Schmitz (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
China's economic rise has transformed the global economy in a number of manufacturing industries. This paper investigates whether China's transformative influence extends to the new green economy. Drawing on the debate about how China is driving major economic changes in the world – the `Asian drivers' debate – it identifies five corridors of influence and investigates their relevance for the wind energy industries. Starting with the demand side, it suggests that the size and rapid growth of the Chinese market have a major influence on competitive parameters in the global wind power industry. While Western firms have found ways of participating in the growth of the Chinese market, the government's procurement regimes benefit Chinese firms. The latter have made big investments and learned fast, accumulating production capabilities that have led to changes in the global pecking order of lead firms. While the combined impact of Chinese market and production power is already visible, other influences are beginning to be felt – arising from China's coordination, innovation and financing power.
Keywords: 330; Energie; Klimawandel; Privatwirtschaft